Language of Evaluation: How PLA Evaluators Write about Student Learning - Travers, Nan L.; Smith, Bernard; Ellis, Leslie; Brady, Tom; Feldman, Liza; Hakim, Kameylah; Onta, Bhuwan; Panayotou, Maria; Seamans, Laurie; Treadwell, Amanda (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
Very few studies (e.g., Arnold, 1998; Joosten-ten Brinke, et al., 2009) have examined the ways in which evaluators assess students’ prior learning. This investigation explored the ways that evaluators described students’ prior learning in final assessment reports at a single, multiple-location institution. Results found four themes; audience, voice, presentation of the learning, and evaluation language. Within each theme, further sub-themes are defined. These results are significant for training evaluators on how to discuss student learning and for institutions to consider in relationship to the purpose behind the evaluations. Further research and implications are discussed.